ALDH2 Polymorphism rs671, but Not ADH1B Polymorphism rs1229984, Increases Risk for Hypo‐HDL‐Cholesterolemia in a/a Carriers Compared to the G/G Carriers. Issue 8 (17th October 2018) - Imatoh, Takuya; Yengo, Loic; Rocheleau, Ghislain; Kamimura, Seiichiro; Maeda, Shiro; Miyazaki, Motonobu; Froguel, Philippe
Abstract: It has been reported that polymorphisms within the gene‐encoding enzymes related to alcohol metabolism are associated with levels of serum HDL‐cholesterol (HDL‐C) in East Asian populations. We evaluated the effects of genetic variants within the aldehyde dehydrogenase‐2 ( ALDH2 ) gene and the alcohol dehydrogenase‐1B ( ADH1B ) gene on changes in the lipid profile in an 11‐year longitudinal study. We genotyped rs1229984 within ADH1B and rs671 within ALDH2 . We combined the genetic data with longitudinal clinical and biochemical data from 2002 to 2013 and designed a retrospective longitudinal study of 1436 Japanese males. There were significant negative relationships between rs671 within ALDH2 and HDL‐C levels according to multiple linear regression analysis. Next, we assessed the association between the development of hypo‐HDL cholesterolemia and rs1229984 within ADH1B or rs671 within ALDH2 . In logistic regression analysis, rs671 A allele homozygote carriers have 2.65 times higher risk of developing hypo‐HDL cholesterolemia than G allele homozygote carriers. Even after adjusting for possible confounding factors, a significant association was observed. However, no association between rs1229984 within ADH1B and the development of hypo‐HDL cholesterolemia was observed. Rs671 within ALDH2 but not rs1229984 within ADH1B was associated with lower HDL‐C levels in Japanese males.